The role of marketing in combating drug abuse: Effective strategies for community awareness and reducing use (Entrepreneurship Journal for Finance and Business, 2024)
This study aims to analyze the effectiveness of social marketing campaigns in combating drug abuse, focusing on their impact on awareness and behavior, particularly among youth. Data were collected through a questionnaire covering four main dimensions: awareness of drug risks, impact of social marketing, illegal drug marketing, and the influence of awareness campaigns on behavior.Results showed that social marketing campaigns play a vital role in increasing public awareness and reaching youth through social media. However, there are challenges in combating illegal online drug marketing. Campaigns influence individual behaviors significantly, but more comprehensive strategies are needed for a broader social impact.The study recommends enhancing collaboration between government and civil society, intensifying efforts to monitor illegal online marketing, and using data analysis to improve campaign performance.